Ecdysis-related pleiotropic neuropeptides expression during Anopheles albimanus development - Alejandro Alvarado-Delgado; Ken Moran-Francia; Guillermo Perales-Ortiz; Mario Henry Rodríguez; Humberto Lanz-Mendoza (Instituto Nacional de Salud Pública, 2017)
Objective. To analyze the transcription pattern of neuropeptides in the ontogeny of a malaria vector, the mosquito Anopheles albimanus. Materials and methods. The transcription pattern of Crustacean CardioActive peptide (CCAP), corazonin, Ecdysis Triggering Hormone (ETH), allatostatin-A, orcokinin, Insulin Like Peptide 2 (ILP2), Insulin Like Peptide 5 (ILP5) and bursicon was evaluated using qPCR on larvae (1st - 4th instar), pupae and adult mosquitoes. Results. Unlike in other insects, transcripts of CCAP (70.8%), ETH (60.2%) and corazonin (76.5%) were expressed in 4th instar larvae, probably because these three neuropeptides are associated with the beginning of ecdysis. The neuropeptide ILP2 showed higher transcription levels in other stages and orcokinin decreased during the development of the mosquito. Conclusion. The CCAP, corazonin and ETH neuropeptidesare potential targets for the design of control strategies aimed at disrupting An. albiamnus larval development.